Intention–behaviour relationship within community running clubs: examining the moderating influence of leisure constraints and facilitators within the environment. Issue 1 (2nd January 2023) - Lower-Hoppe, Leeann M.; Aicher, Thomas J.; Baker, Bradley J.
ABSTRACT: While intention is considered the proximal determinant of behaviour, scholars point to an intention–behaviour gap, calling for research that accounts for the environmental moderators that constrain or facilitate the intention–behaviour relationship. Adopting an ecological perspective, the study examined the potential moderating influence of five leisure constraints and facilitators on the running intention–behaviour relationship within the context of community running clubs. Employing a repeated measures design with members of four community running clubs across the Midwest United States, results of the multi-level modelling indicate running intentions and time significantly predict actual running behaviours. The findings provide no evidence that the leisure constraints and facilitators (leisure constraints, leader autonomy support, perceived motivational climate, club operations and club programmes) influenced the relationship between running intention and running behaviour. These results add further evidence to support the intention–behaviour relationship and suggest this relationship may fluctuate across contexts.